Probiotics effect in prevention and treatment of atopic dermatitis and eczema in children - Vlad Dima; George Iancu; Roxana-Elena Bohiltea; Adrian Ioan Toma; Andreea Avramescu-Calomfirescu; Valentin-Nicolae Varlas; Ana-Maria Davitoiu (Amaltea Medical Publishing House, 2022)
The composition of the intestinal microbiota plays an important role in the occurrence of allergies. Based on the immunomodulating capabilities of bacteria, various studies have investigated the potential role of probiotics in the prevention of eczema and atopic dermatitis in children. Atopic dermatitis (AD) is one of the first manifestations in the evolution of allergies, with a continuously increasing incidence worldwide. In the literature, various risk factors are described to play a role in the occurrence of DA, but the actual cause of the disease is still unknown. The intestinal flora seems to be involved in the development of AD, as patients with AD show quantitative, qualitative and functional changes. An imbalance of the human gut microbiota in the first years of life is a possible risk factor for immune-mediated disorders such as allergies. With the aim of modulating the gut microbiota, probiotic supplementation in the first months of life has been used to prevent allergic diseases in infants, with variable success. However, not much is known about the long-term consequences of the use of probiotics in the newborn on the composition of the gut microbiota. The aim of this paper is to highlight the positive links between the use of probiotics and the prevention or cure of eczema and atopic dermatitis.